SYNTHESIS, ANTIBACTERIAL AND ANTI-INFLAMMATORY ACTIVITIES OF SOME 2-PHENYLGLYOXYLIC ACID DERIVATIVES: Pharmaceutical Science-Pharma chemistry - A. OBAFEMI; TAIWO, FESTUS O.; IWALEWA, EZEKIEL O.; AKINPELU, DAVID A. (International Journal of Life Science and Pharma Research, 2012)
Twelve phenylglyoxylic acid derivatives were synthesized, characterized and investigated for their antibacterial activity against nine Gram-positive and four Gram-negative bacterial isolates. Some of the synthesized compounds exhibited broad spectrum activity against the bacterial strains, with 2-[2-(acetylamino)phenyl]-N- (2-chlorophenyl)-2-oxoacetamide (9) being the most active, having MIC values of 7.8-1000 µg/ml and MBC of 31.3-2000 µg/ ml Seven of the phenylglyoxylic acid derivatives were investigated for their anti-inflammatory activity (acute inflammation, pulmonary oedema and leucocyte counts) in mice. The reduction in oedema formation was between 22-67 % for all the synthesized compounds. The compounds showed significant anti-inflammatory activity with 2-[2-(acetylamino)phenyl]-N-(2,4-dichlorophenyl)-2-oxoacetamide (13) being the most active, while others appear variously dose-dependent